2023
DOI: 10.1063/1674-0068/cjcp2204069
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic evidence for methanol trimer assisted proton transfer: Transient absorption study on excited triplet state of 4-hydroxy-4′-nitrobiphenyl

Abstract: Hydroxyaromatic compounds have a wide range of applications in catalytic synthesis and biological processes due to their enhanced acidity upon photo-excitation. Most hydroxyaromatic compounds with a medium excited state acidity are unable to deprotonate in non-aqueous solvents such as alcohol due to their short-lived excited singlet states. The nitro group in 4-hydroxy-4′-nitrobiphenyl (NO2-Bp-OH) increases the spin-orbit coupling between excited singlet states and the triplet state, resulting in ultrafast int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…34 Experimentally, transient absorption and kinetic analysis results showed that three methanol molecules were required to quench the free triplet followed by the formation of the anion triplet (see the ESI † for experimental and theoretical considerations for choosing the number of Paper PCCP methanol molecules). 18 Therefore, in our QM/MM calculations, the QM subsystem was composed of the NO 2 -Bp-OH chromophore and three hydrogen-bonded methanol molecules nearby the hydroxyl group, which were treated with the CASSCF method; whereas the remaining methanol molecules were all regarded as the MM subsystem and carried out with the modified CHARMM22 force field, referred to as QM(CASSCF)/ MM. 29 In addition, any molecules within 15 Å from the NO 2 -Bp-OH chromophore were allowed to move, while the outermost solvent layer including about 470 methanol molecules were fixed.…”
Section: Calculation Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…34 Experimentally, transient absorption and kinetic analysis results showed that three methanol molecules were required to quench the free triplet followed by the formation of the anion triplet (see the ESI † for experimental and theoretical considerations for choosing the number of Paper PCCP methanol molecules). 18 Therefore, in our QM/MM calculations, the QM subsystem was composed of the NO 2 -Bp-OH chromophore and three hydrogen-bonded methanol molecules nearby the hydroxyl group, which were treated with the CASSCF method; whereas the remaining methanol molecules were all regarded as the MM subsystem and carried out with the modified CHARMM22 force field, referred to as QM(CASSCF)/ MM. 29 In addition, any molecules within 15 Å from the NO 2 -Bp-OH chromophore were allowed to move, while the outermost solvent layer including about 470 methanol molecules were fixed.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…This anion form is consistent with the anion triplet observed in the transient absorption experiment. 18 In addition, as depicted in Fig. 8, we also computed the EPT reactions in the singlet 1 np* and 1 pp* states, which have localized and delocalized (i.e.…”
Section: Excited-state Proton Transfer Reactionsmentioning
confidence: 99%
See 3 more Smart Citations